2019
DOI: 10.1016/j.molcel.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Distinct Pools of TORC1 Balance Protein Homeostasis

Abstract: Graphical AbstractHighlights d Rag GTPases and TORC1 assemble at the surfaces of both endosomes and vacuoles d These spatially and functionally distinct pools of TORC1 target specific effectors d Vacuolar TORC1 promotes protein synthesis through its proximal effector Sch9 d Endosomal TORC1 curbs macro-and microautophagy via Atg13 and Vps27, respectively SUMMARY The eukaryotic TORC1 kinase is a homeostatic controller of growth that integrates nutritional cues and mediates signals primarily from the surface of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
157
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(169 citation statements)
references
References 73 publications
9
157
1
2
Order By: Relevance
“…It is intriguing to observe that in yeast, after TORC1 inactivation, Vph1 is downregulated by ~30-50%. Two other recent publications also made a similar observation (Hatakeyama et al, 2019;Oku et al, 2017). This observation is surprising because, in mammalian cells, it is well established that the v-ATPase components are transcriptionally upregulated by TFEB after MTORC1 inactivation (Sardiello et al, 2009).…”
Section: Different Responses Of V-atpase To the (M)torc1 Inactivationmentioning
confidence: 68%
See 4 more Smart Citations
“…It is intriguing to observe that in yeast, after TORC1 inactivation, Vph1 is downregulated by ~30-50%. Two other recent publications also made a similar observation (Hatakeyama et al, 2019;Oku et al, 2017). This observation is surprising because, in mammalian cells, it is well established that the v-ATPase components are transcriptionally upregulated by TFEB after MTORC1 inactivation (Sardiello et al, 2009).…”
Section: Different Responses Of V-atpase To the (M)torc1 Inactivationmentioning
confidence: 68%
“…S2A-D and S3). These results showed that the ESCRT machinery, but not macroautophagy, is required for the degradation of vacuole membrane proteins (Hatakeyama et al, 2019;Oku et al, 2017;Zhu et al, 2017).…”
Section: The Escrt Machinery Is Required For Invagination Into the Vamentioning
confidence: 90%
See 3 more Smart Citations